The relationship between sedentary behavior, sleep duration, and sleep disorders: analysis of the 2007–2014 National Health and Nutrition Examination Survey - Ju, Keke; Liu, Na; Wu, Ruikai; Shi, Xiujiang (Frontiers in Neurology, 2025)
BackgroundSedentary behavior is closely related to sleep disorders, and long-term lack of physical activity may disrupt circadian rhythms and increase the risk of sleep disorders; Excessive or insufficient sleep time may exacerbate health risks, therefore, analyzing the correlation between sedentary behavior, sleep duration, and sleep disorders.MethodsUsing the NHANES research project, multiple logistic regression analysis was conducted to investigate the relationship between sedentary behavior, sleep duration, and sleep disorders in adults. Restrictive cubic spline curves were used to further explore the dose–response relationship between sedentary behavior, sleep duration, and sleep disorders.ResultsIn the entire study population, compared to the lowest quartile of Sedentary activity duration, the third quartile [OR = 1.441 (95% CI: 1.226–1.693), p < 0.05] and fourth quartile [OR = 1.480 (95% CI: 1.267–1.729), p < 0.05] had an increased risk of developing sleep disorders. Compared with adults who sleep for less than 6 h, those who sleep for 6 to less than 8 h [OR = 0.444 (95%CI: 0.395–0.499), p < 0.05], ≥8 h [OR = 0.370 (95%CI: 0.325–0.422), p < 0.05] the risk of developing sleep disorders decreases. Subgroup analysis found that sedentary behavior and sleep duration have a higher impact on sleep in men under 45 years old. There is a dose–response relationship between sedentary behavior, sleep duration, and the risk of sleep disorders. RCS analysis results show that prolonged sitting for more than 300 min significantly increases the risk of sleep disorders; when the sleep duration is less than 7 h or greater than 8 h, there is a significant increase in the risk of developing sleep disorders. Sensitivity analysis confirmed the robustness of the research results.ConclusionThere is a significant non-linear relationship between sedentary time, sleep duration, and sleep disorders. It is recommended to limit sedentary time to 300 min per day and sleep duration to 7–8 h to reduce the risk of sleep disorders and improve sleep quality.